A practical introduction to the simulation of molecular systems - Field, Martin (Martin J.); Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
Molecular simulation is a powerful tool in materials science, physics, chemistry and biomolecular fields. This updated edition provides a pragmatic introduction to a wide range of techniques for the simulation of molecular systems at the atomic level. The first part concentrates on methods for calculating the potential energy of a molecular system, with new chapters on quantum chemical, molecular mechanical and hybrid potential techniques. The second part describes methods examining conformational, dynamical and thermodynamical properties of systems, covering techniques including geometry-optimization, normal-mode analysis, molecular dynamics, and Monte Carlo simulation. Using Python, the second edition includes numerous examples and program modules for each simulation technique, allowing the reader to perform the calculations and appreciate the inherent difficulties involved in each. This is a valuable resource for researchers and graduate students wanting to know how to use atomic-scale molecular simulations. Supplementary material, including the program library and technical information, available through www.cambridge.org/9780521852524.
Chemical models and representations -- Coordinates and coordinate manipulations -- Quantum chemical models -- Molecular mechanics -- Hybrid potentials -- Finding stationary points and reactions paths on potential energy surfaces -- Normal mode analysis -- Molecular dynamics simulations I -- More on non-bonding interactions -- Molecular dynamics simulations II -- Monte Carlo simulations -- Appendix 1 : the pDynamo library -- Appendix 2 : mathematical appendix -- Appendix 3 : solvent boxes and solvated molecules.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Molecules -- Models -- Computer simulation; Electronic books